(untitled) (Altre Modernità, 2013)
The study examines three novels of apocalyptic character, Cien años de soledad by Gabriel García Márquez, La guerra del fin del mundo by Mario Vargas Llosa and Estrella distante by Roberto Bolaño. Both in Cien años de soledad and in La guerra del fin del mundo apocalypse is related to the sudden and forced graft of modernity in a backward society and to the inability of the ruling class to understand the disturbing and devastating aspects of such a graft and, more generally, to understand themselves, their own development, their own history. Through the metaliterary component that characterizes them, Garcia Marquez’s and Vargas Llosa’ novels represent literature as an instrument that as memory, as a form of processing and understanding of history, can help to prevent the repetition of the apocalypse they narrate. In Bolaño’s novel, on the contrary, writers seem not to have any cognitive power anymore and their literature not only doesn’t play any salvific role, but rather becomes one of the elements that contributes to the historical catastrophe.